Revenge of the Steamroller: ABCP as a Window on Risk Choices. (3rd September 2019) - Arteta, Carlos; Carey, Mark; Correa, Ricardo; Kotter, Jason
Abstract: We use credit-arbitrage asset-backed commercial paper vehicles as a laboratory to empirically examine financial institutions' motivations to take bad-tail systematic risk. By comparing the characteristics of global banks that sponsored credit-arbitrage vehicles prior to the global financial crisis to those that did not, we show that owner–manager agency problems, government safety nets, and government ownership of banks are associated with bad-tail systematic risk-taking. Although good governance is associated with less risk-taking on average, well-governed banks that also have a high ex ante expectation of being bailed out by the government take more risk. Lastly, we find mixed evidence that tougher bank capital regulation deters bad-tail risk-taking.